2018
DOI: 10.7759/cureus.2189
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and Weaning: Practices in Urban Slums of Southern Punjab, Pakistan

Abstract: ObjectiveProper breastfeeding and weaning practices are effective ways of reducing childhood morbidity and mortality. This study aimed to find out breastfeeding and weaning practices among infants of six months to one year in urban slums of Bahawalpur city. By evaluating the knowledge and attitude of lactating mothers regarding their child feeding habits, modifications and specific interventions can be implemented to improve the breastfeeding and weaning practices of the area.MethodsA cross-sectional descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Weaning at 6 months was practiced mostly by the working women as compared to non-working women. 11 In our study, 95% mothers were having high knowledge. Kitiyu P, et al reported that the mean knowledge score was 9.12 ± 1.2 out of possible maximum of 11 (77% high knowledge, 1.1% low knowledge) after delivery.…”
Section: Discussionsupporting
confidence: 45%
“…Weaning at 6 months was practiced mostly by the working women as compared to non-working women. 11 In our study, 95% mothers were having high knowledge. Kitiyu P, et al reported that the mean knowledge score was 9.12 ± 1.2 out of possible maximum of 11 (77% high knowledge, 1.1% low knowledge) after delivery.…”
Section: Discussionsupporting
confidence: 45%
“…They are however lower than the 69.9% of the babies who were weaned at 6 months in our study. On the other hand, in other studies in Jodphur, India [20] and Pakistan [21] 84.28% and 86% of mothers started weaning their babies at the age of 6 months respectively. Early and late initiation of the weaning processes has been associated with different forms of malnutrition and diarrhoea and as such should be discouraged [17,22] .…”
Section: Discussionmentioning
confidence: 73%
“…Majority of mothers, i.e., 63% were housewives and majority of respondents belonged to the middle income group as 41(41%). The analysis showed that 61% mothers had inadequate knowledge about proper child feeding and weaning practice compare with other group as 39% with pvalue 0.01 15 .…”
Section: Discussionmentioning
confidence: 92%